2018
DOI: 10.3892/mmr.2018.9325
|View full text |Cite
|
Sign up to set email alerts
|

Icariin stimulates osteogenic differentiation and suppresses adipogenic differentiation of rBMSCs via estrogen receptor signaling

Abstract: Icariin (ICA) is a major active ingredient in Herba epimedii, which is commonly used as a Chinese herbal medicine for the treatment of osteoporosis. Previous studies have revealed that ICA exerted a protective effect against bone loss and increased bone regeneration; however, the association between ICA and estrogen receptor (ER) signaling remains unclear. The aim of the present study was to determine the effect of ICA on rat bone marrow stromal cells (rBMSCs). Cell Counting Kit‑8 assays were conducted to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…A recent study revealed MIAT was an estrogen-inducible lncRNA and its expression was positively related to estrogen receptor (Li et al, 2018b). There was accumulating evidence to reveal that exposure of bone marrow stem cells to icariin or flavonoids of Herba Epimedii inhibited adipogenic differentiation, exhibiting decreased adipocyte numbers and downregulated mRNA expression of adipogenic differentiation markers, peroxisome proliferator‑activated receptor gamma (PPARγ) and CCAAT/enhancer‑binding protein α (C/EBPα) (Li et al, 2018c; Zhang et al, 2015); while treatment of bone marrow stem cells with estrogen receptor antagonist ICI182780 revered the effects of Herba Epimedii ingredient and promoted adipogenesis (Li et al, 2018c; Zhang et al, 2015). The study of Ihunnah et al (2014) also demonstrated activation of estrogen receptor in ASCs inhibited adipogenesis by decreasing the recruitment of the adipogenic PPARγ onto its target gene promoters, whereas the use of estrogen receptor antagonism ICI 182780 or knockdown of estrogen receptor-α via lentiviral shRNA enhanced adipogenesis by increasing the expression of PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed MIAT was an estrogen-inducible lncRNA and its expression was positively related to estrogen receptor (Li et al, 2018b). There was accumulating evidence to reveal that exposure of bone marrow stem cells to icariin or flavonoids of Herba Epimedii inhibited adipogenic differentiation, exhibiting decreased adipocyte numbers and downregulated mRNA expression of adipogenic differentiation markers, peroxisome proliferator‑activated receptor gamma (PPARγ) and CCAAT/enhancer‑binding protein α (C/EBPα) (Li et al, 2018c; Zhang et al, 2015); while treatment of bone marrow stem cells with estrogen receptor antagonist ICI182780 revered the effects of Herba Epimedii ingredient and promoted adipogenesis (Li et al, 2018c; Zhang et al, 2015). The study of Ihunnah et al (2014) also demonstrated activation of estrogen receptor in ASCs inhibited adipogenesis by decreasing the recruitment of the adipogenic PPARγ onto its target gene promoters, whereas the use of estrogen receptor antagonism ICI 182780 or knockdown of estrogen receptor-α via lentiviral shRNA enhanced adipogenesis by increasing the expression of PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“… 154 Icariin activates the ESR1 signaling pathway; our network pharmacology analysis revealed that its antidepressant effect may be related to the regulation of estrogen signaling. 155 , 157 On the other hand, the decreased GSK-3β phosphorylation detected in the platelets of patients treated for depression implies that GSK-3β hyperactivation contributes to the pathophysiology of depressive disorder; this is underscored by the observation that blocking GSK-3β activity enhanced the effects of antidepressant therapy. 75 , 158 Icariin was been reported to inhibit GSK-3β in part by activating the PI3K/AKT pathway, 76 which may be the mechanism by which it alleviates depressive symptoms.…”
Section: Therapeutic Mechanisms Of Icariin In Nervous System Diseases: Literature Review and Network Pharmacology Analysismentioning
confidence: 99%
“…A recent study found marked activation of ERα and elevated osteogenic activity in both pre-osteoblastic cells and mature osteoblasts after ICA treatment (Zhou et al, 2021), indicating potential links between ERα and the bone preserving effect of ICA. Previous studies also reported that ICA stimulated osteoblast differentiation of bone marrow stromal cells via activation of the ERα signaling pathway, which could be reversed by ERα antagonist (Wei et al, 2016;Li et al, 2018). Additionally, bioinformatic analysis in the present study found that ERα has a close relationship with TNF-α and IL-6, indicating that ERα is a potential regulatory target for CoCrMo particle-induced macrophage activation.…”
Section: Discussionsupporting
confidence: 75%